Functionalized chitosan as a novel support for stabilizing palladium in Suzuki reactions. (15th May 2021) - Dong, Yahao; Bi, Jiajun; Ming, Shujun; Zhang, Shoute; Zhu, Dajian; Meng, Di; Li, Tao
Graphical abstract: Highlights: Schiff base functionalized chitosan decorated with palladium was well synthesized. Excellent capability was obtained towards Suzuki reactions in eco-friendly media. The chitosan supported catalyst exhibited favorable stability and recyclability. A plausibly trifunctional complex structure was also proposed. The study offers a new avenue for polysaccharide utilization in organic catalysis. Abstract: Chitosan is a versatile polysaccharide in different domains due to facile modification and good biodegradability. In this paper, taking advantage of such functional properties, we have developed a stabilizer agent [OCMCS-SB] produced from chitosan, and palladium was successfully immobilized on this designed stabilizer [OCMCS-SB-Pd(II)]. The obtained complex was illuminated by 13 C CP-MAS NMR, FT-IR, TGA, XRD, XPS, SEM, TEM and ICP-OES analyses. Due to the interactions of primary hydroxyl groups on chitosan, Schiff base and carboxy groups, the Pd complex showed excellent reactivity (up to 99 %) and stability towards Suzuki reactions in eco-friendly medium. Subsequently, the reusability experiments for OCMCS-SB-Pd(II) formed from chitosan were examined in five consecutive cycles, which showed no appreciable decrease in activity. Furthermore, a reasonably trifunctional complex structure was proposed. The present bio-based system offers a promising approach in utilizing such biopolymers in organic transformations.